2017
DOI: 10.21273/hortsci11375-16
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest and Sensory Evaluation of Selected ‘Hass’ × ‘Bacon’ and ‘Bacon’ × ‘Hass’ Avocado Hybrids Grown in East-Central Florida

Abstract: Avocado (Persea americana Mill.) is a high-value fruit that continues to increase in consumer demand. A population of ‘Hass’–‘Bacon’ hybrids was planted at USDA-ARS, Fort Pierce, as part of a study to find selections with good horticultural and postharvest quality traits for Florida. Extensive phenotypic data on quality were collected over 3 years. Ten selections were identified in 2014 and 2015 with promising fruit quality and postharvest shelf life characteristics and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 10 publications
3
7
1
Order By: Relevance
“…The maximum fruit weight was obtained from PAKAV009 followed by PAKAV010 (399.2 g) and (338.64 g) respectively. The results of variation in the fruit weight among the genotypes are in agreement with those result by Pisani and Ritenour (2017) where they have reported that there is difference in the weight ranging from 161.8 g to 387.4 g in R8T18 and R5T56 respectively in hybrid reciprocal crosses of 'Hass'-'Bacon'. Similarly, Poudel et al (2017) has also reported that there was variation in fruit weight among pomegranate cultivars from 125.25 g to 355.4 g. The percentage of flesh in the fruits was found difference in the evaluated cultivars of avocado.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The maximum fruit weight was obtained from PAKAV009 followed by PAKAV010 (399.2 g) and (338.64 g) respectively. The results of variation in the fruit weight among the genotypes are in agreement with those result by Pisani and Ritenour (2017) where they have reported that there is difference in the weight ranging from 161.8 g to 387.4 g in R8T18 and R5T56 respectively in hybrid reciprocal crosses of 'Hass'-'Bacon'. Similarly, Poudel et al (2017) has also reported that there was variation in fruit weight among pomegranate cultivars from 125.25 g to 355.4 g. The percentage of flesh in the fruits was found difference in the evaluated cultivars of avocado.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Poudel et al (2017) has also reported that there was variation in fruit weight among pomegranate cultivars from 125.25 g to 355.4 g. The percentage of flesh in the fruits was found difference in the evaluated cultivars of avocado. The result by Pisani and Ritenour (2017) shows that R8T18 (73.7 g) and R5T56 (89.3 g) had the lowest and highest percentage of flesh in avocado fruits, respectively. Our study supports the findings where genotypes PAKAV010 and PAKAV009 had the maximum pulp weight and PAKAV012 had the lowest pulp weight.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The main avocado sensory attributes identified in their work included four texture attributes (firm, creamy, buttery, smooth, and watery) and four flavor attributes (grassy, bland, nutty, and buttery). Moreover, using consumer panels, other authors confirmed the presence of similar attributes in studies with Hass avocado fruit, and in other cultivars reported as Hass hybrids [ 18 , 34 ]. In the aforementioned work, sensory attribute scaled were limited to a creamy texture (watery to creamy), rich (bland to rich), and grassy flavor (grassy to not grassy) on 15-cm line scales.…”
Section: Discussionsupporting
confidence: 66%
“…However, avocado cultivars are reported to differ in their chemical profiles, which can influence their sensory characteristics and consequently, their acceptability. Although consumer liking of some avocado cultivars is reported [ 17 , 18 ], a trained panel-guided identification of the sensory attributes that impact a particular avocado cultivar’s preference over another was not studied. The present work aimed to use predictive modeling to identify potential sensory drivers of liking for avocado pulp by evaluating the acceptability scores and sensory descriptive profiles of two commercial and five non-commercial cultivars.…”
Section: Introductionmentioning
confidence: 99%